1988
DOI: 10.1677/joe.0.1160443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical endurance training on the plasma renin-angiotensin-aldosterone system in normal man

Abstract: The effect of physical endurance training on the plasma renin-angiotensin-aldosterone system was studied in 27 normal sedentary volunteers aged between 20 and 55 years, using a randomized two-period cross-over study design. After 4 months of training (2.5 h/week), peak oxygen uptake and physical working capacity at a heart rate of 130 beats/min were increased by 16% (P less than 0.01) and 29% (P less than 0.001) respectively, whereas resting heart rate was decreased by 15% (P less than 0.001). The plasma norad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 0 publications
0
21
2
5
Order By: Relevance
“…The reduction in plasma aldosterone concentration following the aerobic exercise training programme may be owing to an adaptation of the adrenal gland to adrenocorticotrophin stimulation. 23 It has been shown that adrenocorticotrophin-induced release Values are means7standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in plasma aldosterone concentration following the aerobic exercise training programme may be owing to an adaptation of the adrenal gland to adrenocorticotrophin stimulation. 23 It has been shown that adrenocorticotrophin-induced release Values are means7standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…However, physical training, which leads to a substantial gain in working capacity, does not affect aldosterone levels at rest or at exercise (175). A possible explanation is the suppression of the renin-angiotensin-aldosterone system (RAAS) secondary to training to counteract stress-induced activation (211). The action on baroreflex mentioned above and the reducing effect on heart rate variability (271) may point to an adrenergic-like action of aldosterone.…”
Section: F Mineralocorticoidsmentioning
confidence: 99%
“…Segundo o autor, esse efeito está associado a reduções da ativação simpática, concentrações plasmáticas de angiotensina II e vasopressina. Outros estudos também relatam redução dos níveis de renina e angiotensina II após o treinamento em indivíduos normotensos (HESPEL et al, 1988). Entretanto, em indivíduos hipertensos os estudos ainda não são conclusivos.…”
Section: Mecanismos Envolvidos Na Hipotensão Pós-exercício (Hpe)unclassified